Characterization of the complete mitochondrial genome of the Macaroni penguin Eudyptes chrysolophus from the Barton Peninsula, King George Island, Antarctica - Jong-U Kim; Jeong-Hoon Kim (Mitochondrial DNA. Part B. Resources, 2021)
The Macaroni penguin Eudyptes chrysolophus is a small crested penguin. In this study, the complete mitochondrial genome of E. chrysolophus is revealed for the first time. The mitogenome sequence is circular and 17,059 bp in length. It contains 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, and two ribosomal RNA (rRNA) genes similar to other Spheniscidae species. The total nucleotide composition is 30.53% (A), 32.86% (C), 13.96% (G), and 22.66% (T), and 46.81% for overall GC contents. The phylogenetic analysis shows a close relationship between E. chrysolophus and E. schlegeli. Our findings would be useful for further studies on phylogenetics and evolutionary history of the genus Eudyptes.